Ten-year outcomes in adult patients with congenital heart disease and implantable cardioverter-defibrillators. (15th August 2020) - Brouillard, Adam M.; Al-Hammadi, Noor; Hunt, Craig; Barger, Philip; Ludbrook, Philip; Gleva, Marye Jo
Abstract: Background: Adult congenital heart disease (ACHD) patients may be at risk of sudden cardiac death and be candidates for an implantable cardioverter-defibrillator (ICD). We evaluated the long-term rates of ventricular arrhythmias requiring treatment and mortality in these patients. Methods: A single-center retrospective case-series identified ACHD patients with an ICD and were evaluated for the primary outcome of appropriate ICD intervention or ablation for ventricular tachyarrhythmias. Secondary endpoints were mortality and complication rates. Survival analyses to generate Kaplan-Meier curves for the primary and secondary outcomes were performed. Results: There were 125 adult patients (median age 35.5 years, 68.8% male) with congenital heart disease and an ICD. The median follow-up was 6.4 years (interquartile range 2.8–9.1 years). Transposition of the Great Arteries (TGA) was present in 62 patients (49.6%) and Tetralogy of Fallot (ToF) in 33 (26.4%). The indication for an ICD was primary prevention in 90 patients (72%) and secondary prevention in 35 patients (28%). The primary endpoint occurred in 44 patients (35.2%). Time dependent analyses demonstrated a continual risk of the primary outcome (event rates of 23.8% at 5 years, 45.5% at 8 years, 47.9% at 10 years; p < 0.001). Death occurred in 20 patients (16.0%) and was most commonly from congestive heart failure (CHF). Conclusions: Long-term follow-up of ACHD patients with an ICD experience a persistent risk of ventricular arrhythmias. Mortality was most commonly attributed to CHF. These data provide insight into the clinical course and may guide shared clinical decision making in this complex patient population. Highlights: Adult congenital heart disease patients are at risk for ventricular arrhythmias. Long-term rates of ventricular arrhythmias in these patients are not well known. Patients with Tetralogy of Fallot experienced higher event rates. Mortality was most commonly attributed to congestive heart failure. The most prevalent complication was generator or lead malfunction.